2008
DOI: 10.1037/0090-5550.53.1.18
|View full text |Cite
|
Sign up to set email alerts
|

Driving, aging, and traumatic brain injury: Integrating findings from the literature.

Abstract: Objective: In order to address the potential compounded risk in the population of aging traumatic brain injury (TBI) survivors who continue to drive, the authors synthesized literatures regarding the impact of aging or TBI on driving. Study Design: PubMed searches were conducted utilizing combinations of the following terms: driving, aging, elderly, TBI, cognition, seizures, vision, hearing, rehabilitation, sleep, fatigue, and assessment. Additional sources were also identified from the bibliographies of artic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 89 publications
(169 reference statements)
0
15
0
Order By: Relevance
“…Currently, no specific parameters, protocols, standardized evaluations or regulatory guidelines and mechanisms exist for fail-safe identification of competent drivers after brain injury [5,14,44]. It is hoped that by addressing both the operational (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Currently, no specific parameters, protocols, standardized evaluations or regulatory guidelines and mechanisms exist for fail-safe identification of competent drivers after brain injury [5,14,44]. It is hoped that by addressing both the operational (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found relationships between neuropsychological deficits and driving ability following brain injury. These include visuoperception [6,[13][14][15], attention/ concentration [6,[14][15][16][17][18][19][20][21], speed of information processing [6,14,[16][17][18][20][21][22][23], working memory/ memory [14,16,24] and executive systems [14-18, 20, 22, 24]. In a recent review of the literature, Tamietto et al [16] identified the domains of planning, concentration, inhibition of distractors, foresight, anticipation, problem-solving capacities, the ability to interpret rapidly complex arrays of multimodal stimuli and prompt, effective and calm reactions, as essential elements for driving following traumatic brain injury (TBI).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…TBI residual symptoms may be experienced years after the injury, and can include a variety of difficulties (e.g., daytime sleepiness; fatigue; risk of seizures; cognitive, motor, and sensory deficits) 33 . More importantly, the aging process likely compounds these symptoms.…”
Section: Introductionmentioning
confidence: 99%